A Q-Methodology Study of Patients' Subjective Experiences of TIA. (3rd July 2012) - Spurgeon, Laura; Humphreys, Glyn; James, Gill; Sackley, Cath
Abstract : Background . An expanding body of research has focused on a range of consequences of TIA. However, no work has been conducted on the patient's subjective experience of TIA. Aim . To capture patients' first-hand experiences of TIA. Method . Using Q-methodology which employs both qualitative and quantitative approaches, 39 statements relating to the clinical, physical, affective, and psychological impact of TIA were distilled from the literature and from patient narratives. Consistent with conventional Q-methodology, a purposive sample of twentythree post-TIA patients sorted these statements into a normally-distributed 39-cell grid, according to the extent to which each represented their experience of TIA. Results . Casewise factoranalysis was conducted on the sorted statements. Eight factors emerged which were labelled: lack of knowledge/awareness of TIA; life impact; anxiety; interpersonal impact; depression; physical consequences; cognitive avoidance/denial; constructive optimism. Conclusions . Five of the eight factors confirmed existing research on the impact of TIA, but three new issues emerged: deep-seated anxiety, denial and constructive optimism. The emerging perspectives highlight areas to target in the management of TIA and could inform health education messages, patient information, individualised caremanagement, and enhancement of coping strategies. With development, the findings could be used as a basis for psychometric risk assessment of TIA patients.